Pelaksanaan Perjanjian Pinjaman Yang Memuat Klausula Baku Pada Koperasi Simpan Pinjam Bersinar Pesanggaran - I Wayan Kartika Jaya Utama; I Made Sara; Putu Ayu Sriasih Wesna; Ida Ayu Permata Winditya Dewi; I Putu Wira Dharma Putra Yudha (Postgraduated Community Service Journal, 2024)
The Pesanggaran Shining Savings and Loan Cooperative emerged from the initiative and consensus of a group of people who feel that they have the same needs and interests to move a common capital, especially those that come from deposits and are lent among themselves with an adequate interest rate. Service at the Pesanggaran Shining Savings and Loan Cooperative begins with observations and interviews with the Cooperative Management using socialization, training and mentoring methods as well as evaluation of the implementation of making agreements with standard clauses that have been made. The consequences of null and void laws that will arise against the application of standard clause agreements can be detrimental to the parties, especially cooperatives and customers. With the aim that the management of the Pesanggaran Shining Savings and Loan Cooperative has understood the legal consequences arising from the implementation of the standard clause agreement, it can also overcome the problems of defaulting debtors so that in the future the Pesanggaran Shining Savings and Loan Cooperative can continue to operate without obstacles.